Prevalence of refractive errors and their association with socio demographic characteristics in pediatric patients attending tertiary eye care centre - Choudhary, Sadaf; Kai, Sanjay; Mahajan, Sachit; Sahni, Bhavna; Bala, Kiran (International Journal of Research in Medical Sciences, 2022)
Background: Uncorrected refractive errors are one of the major culprits of visual impairment among children in our country. Children included in school going age groups i.e., 6-16 years, represent 25% of population in developing countries. They fall in the category of preventable age group for correction of refractive errors. This paper describes the salient features and results of the cross-sectional study conducted to determine the prevalence of refractive errors and their association with socio demographic characteristics in pediatric population objective were to study the prevalence of refractive errors and their association with socio demographic characteristics in pediatric patients attending tertiary eye care centre. Methods: The cross-sectional study was conducted for a period of one year among children in 0-16 years age group and a total of 444 patients were included. All children were examined by ophthalmologists and refraction was done by optometrists. Data was analysed using web-based software open epi version 3.01. Results: Prevalence of refractive errors was found to be 29.5%. Amongst the socio demographic factors, there was a significant association of age and literacy with refractive errors whereas gender and residence were not found to be significant. Conclusions: Refractive errors are an important preventable cause of childhood ocular morbidity. Schools are an excellent platform to educate children and their parents regarding eye care and signs of ocular morbidity due to refractive errors. Health education activities in schools need to be intensified.